FAMILY SUPPORT FOR COMPLIANCE WITH COMPLETE BASIC IMMUNIZATION VISITS AT AGE 0-18 MONTHS AT CIKUYA HEALTH CENTER - Tria Monja Mandira; Syeptri Agiani; Windi Puji Astuti (LPPM Universitas Abdurrab, 2025)
Immunization is an effort to actively increase a person's immunity against a disease so that if one day they are exposed to the disease, they will not get sick or only experience mild illness. Since the covid-19 pandemic, basic immunization visits have decreased due to the lockdown as an effort to prevent the transmission of covid-19 with the implementation of physical-social distancing, self-isolation, quarantine, lack of knowledge so that it affects the attitude and support of families in complying with basic immunization visits according to the schedule. Research Objectives: To determine the level of knowledge, attitudes, and family support with compliance with complete basic immunization visits during the pandemic at the Cikuya Community Health Center. Research Methods: This research is an observational quantitative/analytic study with a cross sectional design, data was collected using a questionnaire, the number of samples was 70 respondents. Research Results: It is known that from a total of 70 respondents, more than half of them were 40 respondents (57.1 %) families provide support for immunization and Almost half, as many as 31 respondents (44.3%) were not compliant with immunization visits. The results of the analysis and statistical tests with the chi-square test using the SPSS application, so that it can be concluded that ha is rejected and h0 is accepted and on family support the results are p-value (0.071) Conclusion: Tthere is no relationship between family support and compliance with complete basic immunization visits, Suggestion: The results of this study are expected to be a guideline for increasing information about basic immunization and the importance of complying with basic immunization visits on time to prevent diseases that can be prevented by immunization.